1983
DOI: 10.1007/bf00695061
|View full text |Cite
|
Sign up to set email alerts
|

Cervical tissue shrinkage by formaldehyde fixation, paraffin wax embedding, section cutting and mounting

Abstract: To evaluate the efficacy of cryocoagulation as a treatment for cervical intraepithelial neoplasia (C.I.N.), it is necessary to know the maximum depth of the glandular crypts, the maximum crypt involvement by C.I.N. and the extension of the cryolesion, obtained under standardized conditions. In a morphometric study on this subject, one has to take into account the shrinkage of the cervical tissue, caused by processing the tissue for histological examination. In the present study, tissue shrinkage of the cervix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 4 publications
6
104
4
Order By: Relevance
“…The most likely explanation for z-axis distortion is the physical compression of tissues adjacent to the knife when the knife blade hits the block of tissue (Boonstra et al, 1983). This is thought to result in compression of surface regions of the tissue section more than the core (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…The most likely explanation for z-axis distortion is the physical compression of tissues adjacent to the knife when the knife blade hits the block of tissue (Boonstra et al, 1983). This is thought to result in compression of surface regions of the tissue section more than the core (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, in Siu's study, the tumor itself only shrank 10%, probably resulting from replacement of the contractile esophageal musculature with non-contractile tumor tissue. In a study of uterine cervical tissue by Boonstra et al, 15 fixation in an 8% formalin solution resulted in a 2.7% shrinkage, whereas dehydration, clearing, and paraffin imbedding produced a 12.6% loss of length. They also found that specimen cutting resulted in a slight increase in the horizontal dimension of the margin (0.4%) and that the deep margin was reduced by 2.2%, intuitively corresponding to the crushing effect of perpendicularly oriented force on the knife blade.…”
Section: Discussionmentioning
confidence: 98%
“…In earlier morphometric studies in the cervix, we found that shrinkage of 15% of the specimen had to be taken into consideration. 34 Based on our current results, we have decided to change the intended surgical margins from 1 cm to 2 cm.…”
Section: Discussionmentioning
confidence: 99%